2022
DOI: 10.3390/brainsci12050523
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum-Cortical Interaction in Spatial Navigation and Its Alteration in Dementias

Abstract: The cerebellum has a homogeneous structure and performs different computational functions such as modulation/coordination of the communication between cerebral regions, and regulation/integration of sensory information. Albeit cerebellar activity is generally associated with motor functions, several recent studies link it to various cognitive functions, including spatial navigation. In addition, cerebellar activity plays a modulatory role in different cognitive domains and brain processes. Depending on the net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Also, previous studies have shown FNC variations associated with age within corticocerebellar networks during resting state or the performance of working memory tasks ( 50 ). Although the cerebellum is generally linked with motor processes, it also contributes to executive function, memory, and language ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies have shown FNC variations associated with age within corticocerebellar networks during resting state or the performance of working memory tasks ( 50 ). Although the cerebellum is generally linked with motor processes, it also contributes to executive function, memory, and language ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the current findings could guide future research into assessing the anatomical-functional aspects underlying the ability to detect temporal variations of stimuli. Based on extant evidence from fMRI studies, we have proposed that the inferior olive complex has a critical role in processing the temporal characteristics of visuospatial information ( Mirino et al, 2022 ). For instance, such a proposal matches evidence by Xu et al (2006) , who showed the involvement of subcortical areas, including the inferior olive complex, an area located in the brainstem, in processing temporal characteristics of stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the present findings show that the “Time Squares Sequences” may represent an effective tool to evaluate time processing in visuospatial working memory tasks and that it could be also used to investigate underlying neural mechanisms. Moreover, the task can be successfully used to assess changes occurring with aging, as it can provide useful information on how time is processed during the physiological aging of the individual’s brain as well as during pathological aging (e.g., neurodegenerative illnesses) or following brain injury from head trauma ( Mirino et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cerebellum is more resistant to the neurotoxicity caused by the soluble amyloid-beta (Aβ) protein, as shown by the lower levels of synapse loss in the cerebellum relative to other brain structures [93,94]. During the early stages of AD, the cerebellum compensates with enhanced activity that results in the improvement of some forms of memory [95,96] but the worsening of others, such as the topographic working memory that is functionally related to cerebellar memory [97,98]. The effects of AD on the cerebellum differ from those on other brain structures.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%